Impact of Adjunctive Diode Laser Application to Non-Surgical Periodontal Therapy on Clinical, Microbiological and Immunological Outcomes in Management of Chronic Periodontitis: A Systematic Review of Human Randomized Controlled Clinical Trials - Pawelczyk-Madalińska M; Benedicenti S; Sălăgean T; Bordea IR; Hanna R (Dove Medical Press, 2021)
Magdalena Pawelczyk-Madalińska,1– 3,* Stefano Benedicenti,1 Tudor Sălăgean,4 Ioana Roxana Bordea,5 Reem Hanna1,6,* 1Department of Surgical Sciences and Integrated Diagnostics, Laser Therapy Centre, University of Genoa, Genoa, Italy; 2Department of Periodontology, Pomeranian Medical University, Szczecin, 70-204, Poland; 3FAN-DENT Centrum Stomatologii i Periodontologii, Gdańsk, 80-257, Poland; 4Department of Land Measurements and Exact Sciences, University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, Cluj-Napoca, Romania; 5Department of Oral Rehabilitation, “Iuliu Hațieganu” University of Medicine and Pharmacy Cluj-Napoca, Cluj-Napoca, Romania; 6Department of Oral Surgery, King’s College Hospital NHS Foundation Trust, London, UK*These authors contributed equally to this workCorrespondence: Reem HannaDepartment of Surgical Sciences and Integrated Diagnostics, Laser Therapy Centre, University of Genoa, Genoa, ItalyTel +39 0103537446Email reemhanna@hotmail.comTudor SălăgeanDepartment of Land Measurements and Exact Sciences, University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, Cluj-Napoca, RomaniaTel +40 744707371Email tudor.salagean@usamvcluj.roBackground: Due to the limitations of scaling and root planing (SRP) in chronic periodontitis (CP) management, research has been focused on utilising additional therapies to enhance conventional treatment methods. The present systematic review is aimed to appraise the accessible scientific evidence of in vivo human studies to establish the effectiveness of adjunctive diode (λ 808- λ 980nm) laser treatment to SRP in CP.Methodology: This systematic review was conducted following the PRISMA statement guidelines. The review protocol is registered in PROSPERO (CRD 42021227695). The search strategies were based on structured electronic and manual (with appropriate keywords) and were conducted to collect the applicable published data on RCTs studies (in vivo human), spanning over ten years between August 2010 and August 2020. The articles were selected to address the following research focus question: “Does diode laser (λ 808- λ 980nm) therapy have superior effects as an adjunct to SPR, compared to SRP alone, in terms of clinical or microbiological or immunological profiles in the management of CP?”Results: Fifteen articles met the eligibility criteria and are included in this review. A wide range of discrepancies and inconsistencies were shown in the outcomes of the laser and SPR treatment modality, compared to SRP alone. The data on standardised study protocol, optimal laser parameters and outcome measurements were inconclusive, and a high risk of bias in the majority of the studies observed, which are crucial in establishing a homogenous and reproducible protocol.Conclusion: In light of the confined evidence-based data and critical evaluation of this systematic review, the efficacy of adjunctive diode laser treatment ranging between 808 and 980nm to SRP remains debatable. The observational quality of the present systematic review was emphasised after scrutinising the available data, and an attempt to propose a laser protocol for future RCTs consideration was a great challenge due to an absence of clear and standardised recommendations in delivering a reliable laser protocol which can be replicable by future investigators. RCTs with robust methodology are warranted.Keywords: high intensity laser, diodes laser treatment, chronic periodontitis, systematic diseases, non-surgical periodontal therapy, scaling and root planing, randomised controlled trials studies, RCTs